«#MeToo, és tu?» : incertezas ativistas ontológicas por entre tensões e re-mobilizações portuguesas contra a violência de género no Twitter - Cardoso, Daniel (2025)
The #MeToo movement started on Twitter in 2006, aiming to give visibility to shared narratives of victims of gender-based violence, highlighting its systemic nature. In this sense, technical accessibility to the networked communication platform was an advantage for the dissemination of stories related to the sphere of intimacy, and made it possible to mobilize a specific audience with the ability to occupy technological, social, and discursive space in a highly contested area. This chapter is based on the collection of tweets made until the end of 2022 (inclusive) that contain the hashtag #MeToo, or #EuTambém (Portuguese for "MeToo"), and the word "Portugal" or that were published in Portugal. The aim is to conduct the first complete analysis of the history of this hashtag in Portugal, and to understand how the 'Portuguese-ness' of the use of #MeToo manifests itself. Based on the analysis of the content of the tweets and the network of social actors and reach (through replies, reactions, and shares), we show that: 1) the ontological status of a Portuguese #MeToo, or its mere possibility, is in constant contestation and reaffirmation; 2) corporate media still have a predominant role in pre-defining discursive frameworks on Twitter, creating responsive rather than proactive mobilizations; 3) the discursive performance associated with #MeToo is sometimes accompanied by a non-use of the hashtag, denoting a rejection but not a refusal to participate in the debate.